Monitoreo de pastos marinos en Perezoso, Cahuita, Costa Rica (sitio CARICOMP) - C. Fonseca E., Ana (2007)
The seagrass of Perezoso (Cahuita National Park, Caribbean coast of Costa Rica) was monitored using the CARICOMP proto-col. Productivity (2.7±1.15 g/m2/d; n=74) was intermediate, compared to other Caribbean sites. Total biomass was intermediate to high (750-1500 g/m2) at most CARICOMP sites (Colombia, Cuba, Mexico, Puerto Rico and Venezuela) including Costa Rica (822.8±391.84 g/m2; n=32). Turnover rates were high (5.5±1.36 %; n=74) compared to what was found in March and August at other sites. Shoot densities average 725 shoots/m2, in the Caribbean region, while in Costa Rica the value was higher (1184±335.5 shoots/m2). Average leaf length and width in the entire region were 14.4 cm and 10.6 mm, respectively, similar to what we found, but leaf area index average 3.4 m2m-2, higher than what was found in Costa Rica (0.92 m2m-2). At Cahuita, seagrass productivity was significantly lower in March 2005 compared with the previous six years, and biomass has decreased with time. Seagrass productivity and biomass are being affected by the maximum temperatures, which increased by almost 10 °C from 1999 to 2005, and show a high negative correlation. Turnover rate and temperature were not correlated. Recreational boating, swimming and nutrient loading from deforested lands in the coast, the upstream rivers and local pollution are potential sources of impact to the seagrass beds at Cahuita.